The Effect of Implementation of Lesson Study-Based on Instructional Materials to Enhancing Science Process Skills and Learning Motivation of Students - Hasanuddin Hasanuddin; Cut Nurmaliah; Marlina Marlina (Universitas Syiah Kuala, 2018)
This study aims to develop the 2013 curriculum biology instructional materials based on lesson study and its effect on science process skills and students' learning motivation in Pidie Jaya Regency. The initial stage of this study was to train the biology group teachers from Subject Teacher Association in Pidie Jaya district to develop 2013 curriculum biology instructional materials based on Lesson study. Instructional materialss that are trained based on Lesson Study are: Learning Implementation Plans, Worksheet, and Assessment. The implementation phase of the development of learning devices through activities, namely: 1) General Explanation of the basic principles of lesson study; 2). Workshop on preparing learning too 3). Tests (do) of tool compiled through open lesson at school. 4) Stage of reflection (see) on implementation in class. The study population was class X students of SMAN 1 Meureudu. The sample was determined by 30 students of class X-IPAl of SMAN 1 Meureudu. Data on science process skills and motivation were obtained using questionnaires and analyzed descriptively. Based on the results of the study it is known that the implementation of lesson study based instructional materialss can improve science process skills and learning motivation of class X students of SMA Negeri 1 Meureudu from 3.49 (sufficient) to 4.27 (good).